2015
DOI: 10.3386/w21745
|View full text |Cite
|
Sign up to set email alerts
|

Short-run Effects of Parental Job Loss on Child Health

Abstract: Recent research suggests that parental job loss has negative effects on children's outcomes, including their academic achievement and long-run educational and labor market outcomes. In this paper we turn our attention to the effects of parental job loss on children's health. We combine health data from 16 waves of the Medical Expenditure Panel Survey, which allows us to use a fixed effects specification and still have a large sample of parental job displacements. We find that paternal job loss is detrimental t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…This could lead, ultimately, to increases in undiagnosed and untreated chronic diseases, such as hypertension or heart disease. Of course, it will 2 The reduction in infectious disease is consistent with the findings of Schaller and Zerpa (2015), who use MEPS data to look at the effects of parental job loss on child health and also find reductions in infectious disease among children following displacement. remain difficult to show this directly given that this mechanism relies on undiagnosed conditions.…”
supporting
confidence: 79%
“…This could lead, ultimately, to increases in undiagnosed and untreated chronic diseases, such as hypertension or heart disease. Of course, it will 2 The reduction in infectious disease is consistent with the findings of Schaller and Zerpa (2015), who use MEPS data to look at the effects of parental job loss on child health and also find reductions in infectious disease among children following displacement. remain difficult to show this directly given that this mechanism relies on undiagnosed conditions.…”
supporting
confidence: 79%
“…The vast majority of respondents in our sample reported that at least one immediate family did not currently have health insurance, making them less likely to seek or receive medical treatment (Hacker et al, 2015). Economic and health-related challenges faced by undocumented parents have the potential to trickle down to children and harm their mental health (Schaller & Zerpa, 2019; Gassman-Pines, Ananat, & Fitz-Henley, 2020). In our study, the COVID-19 pandemic has not only made undocumented college students worry about their family’s health and finances, but it has also increased their fears of deportation, detainment, and DACA termination.…”
Section: Discussionmentioning
confidence: 99%
“…Following two recent longitudinal studies using the MEPS (Schaller & Stevens, 2015; Schaller & Zerpa, 2019), we estimated the following difference‐in‐differences specification: yit=αi+Xitβ+γDit+δt+εit, where y it is the outcome of interest for individual i in round t ; α i and δ t represent individual fixed effects and round fixed effects, respectively; and X it is a vector of time‐varying individual and job characteristics. We also controlled for the length of interview round (in days).…”
Section: Empirical Methodsmentioning
confidence: 99%